Protective effect of a novel antioxidant gel containing resveratrol and sodium fluoride on dentin erosion in the presence of acquired salivary pellicle: An in vitro study - Manzoli, Loraine Perez; Silva, Luan Júlio Ruiz da [UNESP]; Caracas, George Clay Dos Santos; de Oliveira, Kalinca Furtado; Aragão, Walessa Alana Braganca; Lima, Rafael Rodrigues; Kuga, Milton Carlos [UNESP]; Alencar, Cristiane de Melo (Elsevier, 2025)
OBJECTIVES: This study aimed to evaluate the protective effect of experimental gels containing resveratrol, with or without 1.23 % sodium fluoride (NaF), and their interaction with the salivary pellicle on dentin erosion. DESIGN: Gels with 5 % or 10 % resveratrol (w/w) were prepared, with NaF added at 1.23 % (w/w). Total polyphenol content (TPC) and antioxidant capacity (ORAC) were determined. Human dentin specimens (n = 210) were allocated into seven groups (n = 30): negative control, NaF (1.23 %), 5 % resveratrol, 10 % resveratrol, 5 % resveratrol + NaF, 10 % resveratrol + NaF, and positive control (commercial anti-erosion toothpaste). Each group was divided according to the presence or absence of salivary pellicle (n = 15). After gel application, specimens were submitted to a 7-day erosive-abrasive cycling protocol. Outcomes included surface loss (3D CLM), collagen degradation after collagenase, calcium release (atomic absorption spectrometry), and tubule obliteration (CLM). Data were analyzed using two-way ANOVA and Tukey's test (α = 0.05). RESULTS: The 10 % resveratrol gel had the highest TPC and ORAC (p = 0.03), followed by 10 % resveratrol + NaF (p = 0.013), whereas 5 % resveratrol showed lower values (p = 0.021). The salivary pellicle significantly reduced dSL-eroded, dColl, and CaR in all groups (p = 0.001). Combined formulations showed the greatest protection: G5 and G6 had lower dSL-eroded (p = 0.002, 0.004), dColl (p = 0.014, 0.021), and dSL-total (p = 0.007, 0.008), with G6 showing the lowest CaR (p = 0.023). CONCLUSION: The combination of 10 % resveratrol and NaF effectively protected against dentin erosion, with salivary pellicle enhancing these effects.